The balloon flights in the tropics of the hibiscus project - Garnier, A.; Pommereau, J. P.; Cocquerez, P.; Held, G. (My University, 2005)
HIBISCUS is a project for studying the dynamics, microphysics and chemistry of the Tropical Tropopause Layer based on balloon measurements. Thirteen heavy sondes and 18 short duration balloons of different types have been used for local process studies. Eight superpressure (BP) and 3 Infra Red Montgolfier (MIR) long duration balloons have been flown for extending the investigations at global scale around the world. Overall the campaign has been very successful operationally as well as scientifically. The paper provides a description of the balloons, the instruments and the strategy used for meeting at best the goals of the project.
Keywords: Aerodynamics; Infrared devices; Project management; Radiosondes; Tropics; Balloon measurements; Tropopause; Meteorological balloons